Synanthropy and ecological aspects of Muscidae (Diptera) in a tropical dry forest ecosystem in Colombia (2010)
ABSTRACT: The synanthropic index and other ecological aspects of the Muscidae family were evaluated through simultaneous monthly sampling in three different environments (urban, rural and forest) using van Someren-Rydon traps baited with human faeces, chicken viscera and decomposing fish and onion. Four traps were set up in each environment (one per bait item) for 48 hours per month, with samples taken every 12 hours. A total of 5726 specimens were collected, belonging to 19 species and 13 genera. Brontaea normata (+99,9), Brontaea quadristigma (+96,9), Synthesiomyia nudiseta (+96,5), Ophyra aenescens (+96,2), Musca domestica (+95,7) and Atherigona orientalis (+93,8) had the highest synanthropic indices, showing a marked preference for human environments. The most abundant species were B. normata (24,31%), Biopyrellia bipuncta (20,60%) and Pseudoptilolepis nigripoda (15,82%), the latter two showed a preference for uninhabited areas. A total of 11 new records for Colombia were found: Ophyra aenescens, Cyrtoneuropsis pararescita, Morellia basalis, Neomuscina dorsipuncta, Biopyrellia bipuncta, Pseudoptilolepis nigripoda, Neomuscina instabilis, Neomuscina currani, Polietina orbitalis, Neomuscina pictipennis and Cyrtoneuropsis maculipennis. Except for the first four species, the remainder presented negative synantrophy indexes (from minor to major), which would allow to use them as ecological indicators of the disturbance degree of dry forests in Colombia.